Symmetric power functoriality for holomorphic modular forms - Newton, J; Thorne, JA (Springer, 2021)
Let 𝑓 be a cuspidal Hecke eigenform of level 1. We prove the automorphy of the symmetric power lifting Sym𝑛𝑓 for every 𝑛≥1.